Meningkatkan Kreatifitas Guru Melalui Pembuatan Media Di Taman Kanak-Kanak - St. Maria Ulfah (Departement of Mathematics Education, 2024)
This study aims to determine how to improve teacher creativity through media making in Kindergarten 23 Rawang Bababulo Majene Regency. This implementation was carried out in February 2022 at TK 23 Rawang Bababulo Majene Regency. The data collection techniques used were observation, interview and documentation. The target of this good practice is 5 people. To solve the problem, several strategies were used, namely: The principal supervises teachers, provides coaching and development, gives rewards to teachers who have high creativity, gives freedom. From the findings of observations made by researchers, there are several teachers who have creativity.